Federalism and economic growth in underdeveloped countries : a symposium - Hicks, Ursula K.; Leverhulme Trust; University of Exeter (New York : Oxford University Press, 1961)
This book is on federalism and economic growth. Based on the papers presented to a working party conference which met at Exeter from September 11 to 14, 1959 ... Sponsored jointly by the Leverhulme Trust and the University of Exeter.
Includes bibliographical footnotes and index.
oo 23/08/2018
Loans
Keywords: Economic development; Newly independent states; Federalism; Developing countries